2012
DOI: 10.1007/s00193-012-0361-3
|View full text |Cite
|
Sign up to set email alerts
|

Aluminum micro-particles combustion ignited by underwater electrical wire explosion

Abstract: The results of experiments on the ignition of aluminum micro-particles' combustion by underwater electrical wire explosion (UEWE) are reported. A compact sub-microsecond timescale duration high-current (240 kA) pulsed power generator was used to explode copper and aluminum wires electrically in different aluminum powder suspensions. The combustion of the aluminum micro-particles was characterized by a target time-of-flight method and optical measurements of the exploding wire and aluminum suspension light emis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…This is explained by the additional energy deposited into the water flow due to Al wire combustion. 14 The simulations also showed that in the case of explosion of the 20 mm-diameter Cu wire array, the state of water P ¼ 10 12 Pa, T ¼ 5 eV, and d ¼ 5 could be realized in the volume with r ¼ 13 lm with a time duration of 17 ns.…”
mentioning
confidence: 81%
“…This is explained by the additional energy deposited into the water flow due to Al wire combustion. 14 The simulations also showed that in the case of explosion of the 20 mm-diameter Cu wire array, the state of water P ¼ 10 12 Pa, T ¼ 5 eV, and d ¼ 5 could be realized in the volume with r ¼ 13 lm with a time duration of 17 ns.…”
mentioning
confidence: 81%
“…Thereby determining the magnitude of the improvements caused by the electrical explosion shockwave stimulation. This will provide basis for theoretical support in engineering applications [49][50][51][52][53][54][55][56][57][58][59][60][61].…”
Section: Mechanism Of Repetitive Pulse Shock Wave Stimulationmentioning
confidence: 99%
“…Extensive work was also published (for example [10, 11] and [12]) on Al powder added to conventional high explosives for increasing their specific energy density, as well as Al nanoparticles suspended in water, a combination termed ‘slurry’, chemically activated by UWEWs (for example [1] and [4]).…”
Section: Introductionmentioning
confidence: 99%